Giant congenital pancreatic cyst in a neonate - Ho Huu Thien; Nguyen Huu Son; Nguyen Thanh Xuan; Mai Trung Hieu; Pham Nguyen Cuong; Vu Hoai Anh (Elsevier, 2021)
Pancreatic cysts in infants are rare. To the best of our knowledge, there are only 38 cases of pancreatic cysts detected among children under 2 years of age. To date, no pediatric case has been reported in Vietnam. Due to its limited incidence, the correct diagnosis and optimal management are still not clearly defined. Here, we present the successful excision of a true congenital pancreatic cyst in a newborn at our center. Literature on this topic was also reviewed.